Phytochemical Study of Cynara scolymus L. (Artichoke) (Asteraceae) Cultivated in Iraq, Detection and Identification of Phenolic Acid Compounds Cynarin and Chlorogenic Acid - Mutalib A.G Nasser, Abdul (Iraqi Journal of Pharmaceutical Sciences, 2017)
The leaves of globe artichoke, Cynara scolymus Family Asteraceae/ compositea have long – used in traditional medicine and now included in British and European Pharmacopeia, the British Harbal Pharmacopeia and complete German Commission E monographs.The plant originally comes from Mediterranean region and North Africa and cultivated around the world. The flowers are used worldwide for nutrition purposes and the leaves for medical purposes including hepatic affections. The plant wildly distributed in Iraq in the watery lines and boundary of the field.The plant contains many phytochemicals such as the bitter phenolic acids whose choleretic and hypocholestremic as these compounds are antioxidant. Other materials to have other pharmacologic effect specially flavonoids. Thus this work deals with phenolic acids cholrogenic acid and cynarin.This work includes cold extraction evaporation by freeze drying and separation inusing column chromatography, TLC and finally in High pressure liqued chromatography (HPLC), the two important compound; chlorogenic acid and cynarin were separated and identified.Key words: Artichoke, Cynara scolymus, Poly phenolic acids, Chlorogenic acid, Cynarin.